MICROBIOLOGICAL EVALUATION OF WATER QUALITY AND SEDIMENTS OF SODA-SALINE LAKES OF THE ZABAIKALYE - E. Yu. Abiduyeva; L. P. Kozyreva; D. D. Tsyrenova; B. B. Namsarayev; B. B. Batobolotova; E. B. Matyugina (Acta Biomedica Scientifica, 2012)
On microbiological and sanitary-bacteriological parameters investigated, include the Zabaikal region lakes to clean, mildly and. moderately polluted, waters. However, in the summer antropogenic pressures on the aquatic ecosystem, of some lakes increases, which, leads to deterioration, of water quality.